Electrolyte Engineering Stabilizes Photoanodes Decorated with Molecular Catalysts. Issue 7 (22nd February 2023) - Jenewein, Ken J.; Wang, Yuanxing; Liu, Tianying; McDonald, Tara; Zlatar, Matej; Kulyk, Nadiia; Benavente Llorente, Victoria; Kormányos, Attila; Wang, Dunwei; Cherevko, Serhiy
Abstract: Molecular catalysts are promising oxygen evolution promoters in conjunction with photoanodes for solar water splitting. Maintaining the stability of both photoabsorber and cocatalyst is still a prime challenge, with many efforts tackling this issue through sophisticated material designs. Such approaches often mask the importance of the electrode‐electrolyte interface and overlook easily tunable system parameters, such as the electrolyte environment, to improve efficiency. We provide a systematic study on the activity‐stability relationship of a prominent Fe2 O3 photoanode modified with Ir molecular catalysts using in situ mass spectroscopy. After gaining detailed insights into the dissolution behavior of the Ir cocatalyst, a comprehensive pH study is conducted to probe the impact of the electrolyte on the performance. An inverse trend in Fe and Ir stability is found, with the best activity‐stability synergy obtained at pH 9.7. The results bring awareness to the overall photostability and electrolyte engineering when advancing catalysts for solar water splitting. Abstract : In the nick of time : Highly active and corrosion‐resistive hybrid photoelectrodes are crucially needed to significantly advance solar water splitting. A detailed activity‐stability study of a promising Fe2 O3 photoanode decorated with an Ir molecular catalyst is highlighted by employing operando mass spectrometry. Electrolyte engineering in the form of pH adjustments is presented as a facile approach to stabilize the photoabsorber and cocatalyst.